Islamic glazed wares from ancient Termez (southern Uzbekistan). Raw materials and techniques. (February 2020) - Molera, Judit; Martínez Ferreras, Verònica; Fusaro, Agnese; Gurt Esparraguera, Josep M.; Gaudenzi, Mainardo; Pidaev, Shakir R.; Pradell, Trinitat
Highlights: The chemical, mineralogical and petrographic composition of glazed wares from Termez is examined. The local–regional vessels from the 9th-11th c. contain lead transparent glaze over a clayey slip. The 12th-17th c. local wares have alkaline glazes, white slips with large quartz and feldspar grains. Abstract: Ancient Termez, located on the southern border of Transoxiana/Mawarannahr, was an important pottery production centre during the Islamic period. Recent archaeological and archaeometric research carried out by the Spanish-Uzbek team evidenced the manufacture of glazed and unglazed vessels at the workshops found in the lower city (shahristan) and its suburbs (rabad). Glazed local products, mainly dated between the 9th and 16th/17th centuries, comprise slip-painted, underglaze and inglaze painted wares, splashed sgraffiato, and monochrome wares. The present study focuses on the chemical, mineralogical and petrographic examination of different types of glazed ceramics recovered at Termez excavations in order to identify the microstructure and composition of the glazes, the technological processes involved in their manufacture, and their evolution over the centuries. Thin polished sections were prepared and slips and glazes were analysed by optical microscopy (OM) and scanning electron microscopy (SEM). The results reveal that all the local/regional ceramics have a slip and a transparent glaze, with one exception. Colour decorations were applied over the slip, forming thinner or thicker layers depending on the desired final colour. Green (copper), red (iron) and brown/black (iron and in some cases iron plus manganese) pigments were used for the decorations. A high lead glaze was used in the ceramics found in the alluvial plain dating between the 9th and the 11th century, while an alkaline glaze is associated with the majority of ceramics collected in the shahristan dating between the 12th and the 17th century. An alumina rich clay mixed with lead oxide was used in the slip from the alluvial plain ceramics while the slip contained large quartz grains in the ceramics found in shahristan. Three imports from the Iraqi regions, a monochrome lustreware bowl and two white opaque glazed dishes dating from the 9th–10th centuries, were also analysed. They have the characteristic tin-opacified mixed lead-alkali glazes and fine calcareous pastes.